2009
DOI: 10.1002/chem.200801446
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Thiosemicarbazides with Redox Active Metal Ions: Controlled Formation of Coordination Complexes versus Heterocyclic Compounds

Abstract: The reactions of 1,1-dimethyl-4-phenylthiosemicarbazide (LH) with Cu(II) and Sn(IV) have been investigated. If THF or methanol is used as solvent with Cu(II), oxidative cyclisation and coupling are observed, yielding a 1,2,4-thiadiazole or a 1,3,4-thiadiazolium salt. SnI(4) is also able to induce oxidative coupling of two thiosemicarbazide ligands, yielding 1,2,4-thiadiazolium or 1,2,4-triazolium salts, with I(3)(-) as the counterion, depending on the reaction conditions. By contrast, reaction of LH with SnI(4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…The twist in the molecule is confirmed by the dihedral angle between the phenyl rings of 71.07(4)°. As for the literature structures [5,6] The structure of the present compound is isostructural with the 4-Me analogue [6]. As anticipated, equivalent intermolecular interactions are present in both crystals with the additional C5-Cl1• • • π(phenyl-C2-C7) contact obviously lacking in the 4-Me structure.…”
Section: Commentsupporting
confidence: 75%
See 1 more Smart Citation
“…The twist in the molecule is confirmed by the dihedral angle between the phenyl rings of 71.07(4)°. As for the literature structures [5,6] The structure of the present compound is isostructural with the 4-Me analogue [6]. As anticipated, equivalent intermolecular interactions are present in both crystals with the additional C5-Cl1• • • π(phenyl-C2-C7) contact obviously lacking in the 4-Me structure.…”
Section: Commentsupporting
confidence: 75%
“…Recent structural studies of molecules of the general formula Me(R)NN(H)C(=S)N(H)(PhY-4) have revealed a high degree of homogeneity in terms of the adopted molecular geometry and in the formation of supramolecular synthons of the type {• • • HNCS} 2 owing to the syn disposition of the thione-S and thioamide-N-H atoms [5,6]. The main motivations for investigating such di-substituted thiourea derivatives comes about owing to their utility in asymmetric synthesis as dual hydrogen bonding catalysis [7] and their pharmaceutical potential [8].…”
Section: Commentmentioning
confidence: 99%
“…There is a closely related structure in the literature where the N-bound phenyl group of (1) is substituted by a methyl group and the original 4-tolyl ring is now a phenyl ring, that is, Me2NN(H)C(=S)N(H)Ph (2) [7]. Molecule (2) adopts essentially the same conformation as just In the crystal of (1), the most prominent feature of the molecular packing is the formation of thioamide-N1-H• • • S1(thione) hydrogen bonds.…”
Section: Resultsmentioning
confidence: 99%
“…The melting point was determined on a Biobase automatic melting point apparatus MP450 (Biobase Group, Jinan, Shandong Province, China). The IR spectrum was measured There is a closely related structure in the literature where the N-bound phenyl group of (1) is substituted by a methyl group and the original 4-tolyl ring is now a phenyl ring, that is, Me 2 NN(H)C(=S)N(H)Ph (2) [7]. Molecule (2) adopts essentially the same conformation as just described for (1) but, some systematic changes in the key bond lengths are evident.…”
Section: General Informationmentioning
confidence: 99%
“…[1][2][3][4][5]), as well as owing to their unique role in self-organization of potential metalorganic complexes through coordination to different transition metal ions [6][7][8][9][10][11]. For example, 2-amino-1,3,4-thiadiazole easily undergoes a transition-metalinduced reductive coupling reaction with acetonitrile, resulting in Co(III) amidine complexes [6], while the bis(5-anilino-3-methyl-1,3,4-thiadiazol-3-ium) tetrachlorocuprate(II) salt has been prepared in a good yield by a Cu(II)-induced reaction of a thiosemicarbazide precursor (PhNHCSNHNMe 2 ) with CuCl 2 [11]. Despite the considerable interest in 1,3,4-thiadiazole derivatives, the research area of their complexation with copper halides is still rather poorly covered and the only hitherto synthesized and X-ray studied copper(I) chloride complex is [Cu(L2)Cl] (2) (L2 = 2-amino-5-methyl-1,3,4-thiadiazole) [12].…”
Section: Introductionmentioning
confidence: 99%